[OP.5D.05] IMPAIRED SKELETAL MUSCLE OXYGENATION AND ENDOTHELIAL FUNCTION IN WOMEN WITH GESTATIONAL DIABETES MELLITUS ASSESSED BY NEAR- INFRARED SPECTROSCOPY. (September 2016) - Dipla, K.; Kintiraki, E.; Grigoriadou, I.; Triantafyllou, G.; Triantafyllou, A.; Zografou, I.; Vrabas, I.S.; Zafeiridis, A.; Goulis, D.G.; Douma, S.
Abstract : Objective: Patients with Gestational diabetes mellitus (GDM) are at increased risk for gestational hypertension. Although GDM is considered a mild metabolic dysfunction, some studies have associated GDM with alterations of endothelial responsiveness, whereas, other studies suggested that the time of exposure to hyperglycemia might be insufficient to induce micro- and macrovascular dysfunction. Near-infrared spectroscopy (NIRS) allows a non-invasive monitoring of functional changes in oxygenated hemoglobin (O2Hb) and oxygen tissue saturation (TSI) and the assessment of microvascular function within the skeletal muscle. This study aimed to investigate whether differences in skeletal muscle oxygen utilization (VO2) and microvascular endothelial function exist between GDM and uncomplicated pregnancies, using NIRS monitoring. Design and method: Twenty-nine pregnant women (13 with GDM and 16 age- and parity-matched women with uncomplicated pregnancies, gestational age 26–30 weeks) were participated in the study. Continuous dual-wavelength NIRS (Artinis) monitored changes in muscle O2Hb and TSI. The experimental procedure included: a) baseline measurements, b) vascular occlusion: 5-min brachial arterial occlusion was applied for assessing the maximal capacity for O2 extraction by the skeletal muscles (mitochondrial function), and c) re-oxygenation: kinetics and degree of hyperemia were recorded for assessing vascular responsiveness (endothelial function) in the micro-circulation. Results: During occlusion, the magnitude of decline in TSI was significantly smaller (−16.05 ± 6.71 vs. −25.90 ± 9.81; p < 0.01) and the rate of de-oxygenation was slower in women with GDM than controls (p < 0.01). During re-oxygenation, the magnitude of TSI rise was smaller (22.86 ± 9.31vs. 35.35 ± 11.87, respectively; p < 0.01) and the rate of re-oxygenation was slower in women with GDM than controls (p < 0.01). The skeletal muscle VO2 and the magnitude of hyperemic response were also lower in women with GDM than controls (p < 0.01). Conclusions: The blunted skeletal muscle TSI responses during ischemic occlusion and hyperemia in women with GDM vs. controls indicate that GDM is characterized by (i) alterations in the dynamic balance of O2 delivery-utilization in the microcirculation and in the diffusion of O2 from capillaries to myocytes, (ii) a lower muscle oxidative capacity, and (iii) reduced vascular responsiveness and altered endothelial function in microcirculation.